2015
DOI: 10.1103/physrevb.92.224407
|View full text |Cite
|
Sign up to set email alerts
|

Band-gap narrowing in Mn-doped GaAs probed by room-temperature photoluminescence

Abstract: The electronic band structure of the (Ga,Mn)As system has been one of the most intriguing problems in solid state physics over the past two decades. Determination of the band structure evolution with increasing Mn concentration is a key issue to understand the origin of ferromagnetism. Here we present room temperature photoluminescence and ellipsometry measurements of Ga 100%-x Mn x As alloy. The up-shift of the valence-band is proven by the red shift of the room temperature near band gap emission from the Ga … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
1
7
1
Order By: Relevance
“…The high concentration of S at the surface region (the S concentration higher than 10 19 cm −3 ) is due to the measurements instability during the initial stage of sample sputtering (first 10 nm). The similar distribution phenomena has been reported for Mn implanted GaAs layers annealed by ms‐range FLA . Note that the diffusion coefficient of S at 900 °C in GaAs is in the range of 1 × 10 −11 cm 2 s −1 , and is comparable to the diffusion of Zn in GaAs (1.7 × 10 −11 cm 2 s −1 ) .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The high concentration of S at the surface region (the S concentration higher than 10 19 cm −3 ) is due to the measurements instability during the initial stage of sample sputtering (first 10 nm). The similar distribution phenomena has been reported for Mn implanted GaAs layers annealed by ms‐range FLA . Note that the diffusion coefficient of S at 900 °C in GaAs is in the range of 1 × 10 −11 cm 2 s −1 , and is comparable to the diffusion of Zn in GaAs (1.7 × 10 −11 cm 2 s −1 ) .…”
Section: Resultssupporting
confidence: 82%
“…Moreover, proper defect engineering in GaAs leads to a 1.3 μm emission, which is attractive in the field of optical‐fiber communications . Prucnal et al have also studied the evolution of the electronic band structure in (Ga,Mn)As after FLA. It has been shown that using Mn implantation followed by FLA up to 0.6% of Mn can be incorporated into the GaAs crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows that considerable polarization and transmission is obtained for b~1.5 nm. This value of inter-Mn separation is not drastically different from 4 nm observed in the experiment 63 . Therefore, we expect that effects considered in the current paper are within reach with currently available experimental techniques.…”
Section: Discussioncontrasting
confidence: 49%
“…While there has been a wide range of semiconductor material systems that have been used as hosts, the choices for the magnetic dopants have been mainly transition metals, such as first row metals (Mn 2+ , Co 2+ , Ni 2+ , Cu 2+ ) and lanthanides (Eu 2+ , Er 3+ , Sm 3+ , Yb 3+ ). , Out of these, there has been extensive work on the incorporation and effects of Mn 2+ . , This includes structural and chemical changes, dopant destination (spatially), and energy transfer dynamics of the host to Mn 2+ that results in a signature 580–600 nm emission. Prominent host materials have been Zn­(S,Se,O) , or Cd­(S,Se) , nanocrystals and quantum dots, or III–V semiconductor films and nanowires. Notable performance improvements in optoelectronic applications of these semiconductors in solar cells and hot electrons for photocatalysis have been reported. However, more intriguing has been the observation of magneto-optical and magneto-transport properties, which includes high temperature ferromagnetic semiconductors (up to 425 K for doping <4 at%), spin injection, and spin polarized emission for potential spintronics.…”
mentioning
confidence: 99%